Sensitivity Analysis of Feasibility Investment of Electric Motorcycle in Online Drivers in DKI Jakarta - Marendra I Gede; Aryata I Made (Enrichment : Journal of Management, 2022)
The high number of motorcycle users in DKI Jakarta in 2022 as many as 16,734,986 units causes poor air quality in DKI Jakarta with an AQI US value of 145. The mobility of online motorcycle drivers with an average daily distance of 230 km/day also contributes to the level of air pollution in DKI Jakarta. Through the COP26 World Climate Change Conference in Glasgow in 2021, The Indonesian government is targeting a 29% reduction in Greenhouse Gas (GHG) emissions independently and 41% with international assistance by 2030. One way is through the conversion of electric motorcycles for online motorcycle drivers, with the conversion of electric motors, it is expected to reduce air pollution in DKI Jakarta and support the achievement of 13 million electric motor units by 2030. Based on the results of the analysis, it is known that the investment in electric motorbikes made by online motorcycle drivers is said to be feasible because it provides an NPV of Rp. 2,757,262,- and IRR of 14,05%. By performing sensitivity on several variables, the maximum limit of change for each variable is 5% for the increase in the IRR of motorcycle installments, 9% for the increase in the IRR of battery installments and 10% for the increase in the price of the battery. If there is a simultaneous increase in the three variables, the maximum limit for the increase is 1% for the increase in the IRR for motorcycle installments, 1% for the increase in the IRR for battery installments and 10% so that the NPV can be Rp. 340.108,- and IRR of 10.48%.